1998
DOI: 10.1016/s0022-2275(20)32479-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnancy and lactation on lipoprotein and cholesterol metabolism in the rat

Abstract: Origins of hyperlipidemia and cholestasis that occur during pregnancy were investigated by examining expression of key elements related to plasma and hepatic cholesterol metabolism during pregnancy, lactation, and post-lactation in the rat model. Among major findings were: during pregnancy, the activities of hepatic 3-hydroxy-3methylglutaryl coenzyme A reductase, acyl coenzyme A:cholesterol acyltransferase, acyl coenzyme A:diacylglycerol acyltransferase, cholesterol 7 ␣ -hydroxylase, cholesterol ester hydrolas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Animal studies have demonstrated that breastfeeding plays an important role in mobilizing stored fat, 24 reestablishing glucose homeostasis, 24 , 25 regulating insulin secretion, 26 and promoting lipid metabolism after delivery. 27 Population evidence from observational studies also suggests that breastfeeding is associated with improved glucose metabolism and pancreatic beta-cell function, 28 more favourable lipid profiles, 29 and reduced weight loss and risk of metabolic diseases. 30 Meanwhile, several randomised controlled trials have demonstrated that greater intensity of lactation is associated with greater postpartum weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that breastfeeding plays an important role in mobilizing stored fat, 24 reestablishing glucose homeostasis, 24 , 25 regulating insulin secretion, 26 and promoting lipid metabolism after delivery. 27 Population evidence from observational studies also suggests that breastfeeding is associated with improved glucose metabolism and pancreatic beta-cell function, 28 more favourable lipid profiles, 29 and reduced weight loss and risk of metabolic diseases. 30 Meanwhile, several randomised controlled trials have demonstrated that greater intensity of lactation is associated with greater postpartum weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of a 21-day lactation, a female mouse nursing a large litter will produce about 20 g of milk fat, containing about 100 mg of cholesterol. Smith et al (29) studied the effect of lactation on plasma lipoproteins in rats. Whereas the LDL content of plasma was increased in lactation, very low density lipoprotein (VLDL)-sized particles were not apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Acyl coenzyme A:cholesterol acyltransferase (ACAT ) localized largely in the RER (35,36) and acyl coenzyme A:diacylglycerol acyltransferase (DGAT ) localized in both RER and smooth ER (37,38) were measured by enzyme activity as described previously (39). Albumin, and apolipoproteins A-I, E, A-IV, and C were estimated in aliquots of whole liver homogenate and intact RER by SDS gel electrophoresis and Western blotting using specific antisera provided by Dr. Karl Weisgraber as described previously (28).…”
Section: Lipoprotein Assembly Proteins and Enzymesmentioning
confidence: 99%
“…Albumin, and apolipoproteins A-I, E, A-IV, and C were estimated in aliquots of whole liver homogenate and intact RER by SDS gel electrophoresis and Western blotting using specific antisera provided by Dr. Karl Weisgraber as described previously (28). ApoB was estimated by SDS gel electrophoresis and Western blot as described previously (39). Microsomal triglyceride transfer protein (MTP) was estimated by SDS gel electrophoresis and Western blot using specific antisera for MTP pro-vided by Dr. David Gordon.…”
Section: Lipoprotein Assembly Proteins and Enzymesmentioning
confidence: 99%